Performance of crispy lettuce cultivars in different soil covers - Vargas, Pablo Forlan [UNESP] (2017)
The lettuce cropping is an important segment of the national agriculture, with strong economic expression. However, climatic factors such as high temperature and humidity can affect this vegetable cultivation. These environmental conditions are common in various Brazilian regions, so the growers should adopt crop management systems, as soil covers, to minimize the environmental effect and obtain higher returns. Thus, the aim of this study was to evaluate the influence of different soil covers on the agronomic performance of crispy lettuce cultivars. The study was conducted at UNESP, Registro Campus, Brazil, from August to October, 2013. The experiment was carried out in a randomized blocks design, arranged in a 4x4 factorial, with three repetitions. The treatments consisted of the factors soil covers (black mulching, silver mulching, white mulching and control) and cultivars (Inaiá, Milena, Vanda and Vera). The experimental unit consisted of fifteen plants, with the useful area composed of nine central plants. At harvest, the following characteristics were evaluated: plant height, head diameter, fresh mass, number of leaves, leaf width, leaf height, stem diameter, heart diameter, heart height, dry mass, yield and nitrate content. Among the studied covers, white mulching showed the best results for the main productive characteristics and can be used as soil cover in the cultivation of Vera, Vanda and Inaiá culivars.